Prevalence of Urine for Microalbumin in Type 2 Diabetes: A Descriptive Cross-Sectional Study in A Tertiary Care Hospital - BK, Shyam Kumar; K.C., Balaram; Dhakal, Aarati; Paudel, Sakar; Sonar, Arjun Sah (Journal of Nepalgunj Medical College, 2025)
Introduction: Microalbuminuria is an early clinical indicator of diabetic nephropathy and a predictor of cardiovascular morbidity and mortality in patients with type 2 diabetes mellitus (T2DM). Early detection is vital for timely management to prevent progression to overt nephropathy and renal failure. Aims: To determine the prevalence of microalbuminuria and its association with glycemic control, blood pressure, and body mass index with type 2 diabetes mellitus. Methods: A descriptive cross-sectional study was conducted at Nepalgunj Medical College, from October 2024 to April 2025. Two hundred patients with confirmed type 2 diabetes mellitus of at least one-year duration were enrolled using convenience sampling. Patients with urinary tract infections, pregnancy, or non-diabetic renal diseases were excluded. Demographic data, clinical parameters, and laboratory results including fasting blood sugar, HbA1c, lipid profile, and urine microalbumin levels were recorded. Statistical analysis was performed using SPSS version 25. Student’s t-test and Chi-square test were applied, and p-value <0.05 was considered statistically significant. Results: Among 200 participants, 30 (15%) had microalbuminuria. The mean age of participants with microalbuminuria (65.07 ± 15.05 years) was higher than those without (52.95 ± 13.34 years). Microalbuminuria was more prevalent among females (9.5%) compared to males (5.5%). Participants with microalbuminuria had significantly higher HbA1c (8.30 ± 1.57%) and mean random blood sugar levels was (238.23 ± 25.607) . Individual without microalbuminuria had HbA1c (7.22 ± 1.065%) and mean random blood sugar level was (218.15 ± 46.60). The prevalence was greater among obese individuals and those with stage 2 hypertension. Serum cholesterol and triglyceride differences were not statistically significant. Conclusion: The prevalence of microalbuminuria among patients with type 2 diabetes was 15%. Poor glycemic control, hypertension, and obesity were significantly associated with its occurrence.